BUSINESS-PLAYING AS AN INTERACTIVE FORM OF FOREIGN LANGUAGE LEARNING IN THE CONTEXT OF HIGHER ENGINEERING EDUCATION - Bryntseva, O.; A., Podorozhna (Problems of Engineer-Pedagogical Education, 2023)
The article is devoted to the issues of business games creation and implementation in the process of teaching a professionally oriented foreign language at engineering universities. It has been determined that in the context of teaching a foreign language to engineering students, a business game develops foreign language communication skills, thus forming not only professional competence, but also communicative competence; it reproduces the subject and social content of students' future professional activities, forms a system of relations typical for specialists in the relevant field. Therefore, in the learning process through business games, students provide substantive content to foreign language communication, integrate their professional skills into foreign language skills, master the ability to build social relationships, learn to overcome conflict situations and respond adequately to changing circumstances. The article presents an example of the methodological development of the business game "Innovations in the Energy Sector", which was tested at the Department of Foreign Language Training, European Integration and International Cooperation in partnership with the Department of Automation, Metrology and Energy Efficient Technologies (UEPA, Kharkiv). The experience of using business games in the process of foreign language learning at an engineering university allowed the authors to identify their specific features: using special didactic, methodological and technical support; careful preparation of speech materials; activation of students' independent work at the preparatory stage; selection of tasks in such a way as to stimulate independent training in business games not only to master new foreign language vocabulary (including terminology), but also to model various styles of speech (including terminology). The article concludes as follows: using game-based learning increases students' motivation to learn foreign languages and cultures, prepares them for practical foreign language skills in real life and in their future professional activities.